Siedemnastowieczna polszczyzna kijowska w panegirykach Stefana Jaworskiego - Klimek-Grądzka, Jolanta (Forum Lingwistyczne, 2019)
The article discusses a regional variety of Polish spoken in Kiyv preserved in the Polish-Latin panegyrics composed by Stefan Jaworski (1656(8)–1722) to venerate Warłam Jasiński. The analysis aims at drawing a catalogue of phonetic, inflectional, word formation and syntactic idiolectal features of this variety as juxtaposed against the 17th century standard Polish. The analysis reveals the poet’s fluency in a language that was foreign (second) to him. This fluency also covers the poet’s skill in using varietal forms to achieve artistic aims. The regional forms subject to the study often display closeness to the ones in the Borderland variety of Polish, yet with an idiolectal inflectional features, e.g.: a large number of participles ending in -owszy or frequent cases of l/ł alternation.